Glenoid Dysplasia: Pathophysiology, Diagnosis, and Management. (1st June 2016) - Eichinger, Josef K.; Galvin, Joseph W.; Grassbaugh, Jason A.; Parada, Stephen A.; Li, Xinning
Abstract : Subtle forms of glenoid dysplasia may be more common than previously thought and likely predispose some patients to symptomatic posterior shoulder instability. Severe glenoid dysplasia is a rare condition with characteristic radiographic findings involving the posteroinferior aspect of the glenoid that often remains asymptomatic. Instability symptoms related to glenoid dysplasia may develop over time with increased activities or trauma. Physical therapy focusing on rotator cuff strengthening and proprioceptive control should be the initial management. Magnetic resonance imaging and computed tomographic arthrograms are useful for detecting subtle glenoid dysplasia by revealing the presence of an abnormally thickened or hypertrophic posterior part of the labrum, increased capsular volume, glenoid retroversion, and posteroinferior glenoid deficiency. Open and arthroscopic labral repair and capsulorrhaphy procedures have been described for symptomatic posterior shoulder instability. Glenoid retroversion of >10° may be a risk factor for failure following soft-tissue-only procedures for symptomatic glenoid dysplasia. Osseous procedures are categorized as either glenoid reorientation (osteotomy) or glenoid augmentation (bone graft), and no predictable results have been demonstrated for any surgical strategy. Glenoid osteotomies have been described for increased retroversion, with successful results, although others have noted substantial complications and poor outcomes. In severe glenoid dysplasia, the combination of bone deficiency and retroversion makes glenoid osteotomy extremely challenging. Bone grafts placed in a lateralized position to create a blocking effect may increase the risk of the development of arthritis, while newer techniques that place the graft in a congruent position may decrease this risk.